2001
DOI: 10.3348/kjr.2001.2.4.183
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted MR Imaging of Intracerebral Hemorrhage

Abstract: ObjectiveTo document the signal characteristics of intracerebral hemorrhage (ICH) at evolving stages on diffusion-weighted images (DWI) by comparison with conventional MR images.Materials and MethodsIn our retrospective study, 38 patients with ICH underwent a set of imaging sequences that included DWI, T1-and T2-weighted imaging, and fluid-attenuated inversion recovery (FLAIR). In 33 and 10 patients, respectively, conventional and echo-planar T2* gradient-echo images were also obtained. According to the time i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
115
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(127 citation statements)
references
References 23 publications
12
115
0
Order By: Relevance
“…In general, late subacute intracerebral hematoma appears as high intensity on both T 1 -and T 2 -weighted imaging, reflecting lysis of the erythrocytes and predominantly extracellular methemoglobin. [2][3][4] The mean ADC value of the extracellular methemoglobin is 0.58 ± 0.10 × 10 -3 mm 2 /sec. 4) The high intensity areas in the subacute hematoma on diffusion-weighted imaging were considered to mainly consist of extracellular methemoglobin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, late subacute intracerebral hematoma appears as high intensity on both T 1 -and T 2 -weighted imaging, reflecting lysis of the erythrocytes and predominantly extracellular methemoglobin. [2][3][4] The mean ADC value of the extracellular methemoglobin is 0.58 ± 0.10 × 10 -3 mm 2 /sec. 4) The high intensity areas in the subacute hematoma on diffusion-weighted imaging were considered to mainly consist of extracellular methemoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] The mean ADC value of the extracellular methemoglobin is 0.58 ± 0.10 × 10 -3 mm 2 /sec. 4) The high intensity areas in the subacute hematoma on diffusion-weighted imaging were considered to mainly consist of extracellular methemoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…3) In this study, 29 of the 31 chronic subdural hematomas showed low intensity components on diffusion-weighted imaging due to the free water molecular movement rather than the paramagnetic effect of the extracellular methemoglobin, because the ADC value (1.81 ± 0.79 × 10 -3 mm 2 /sec) of the low intensity areas was larger than the reported ADC value of extracellular methemoglobin (0.58 ± 0.10 × 10 -3 mm 2 /sec). 8) The high intensity areas in the present subdural hematomas consisted of several types: high intensity line along the dura mater (subdural hyperintense band), high intensity along the intrahematoma septum, and laminar shape along the inner membrane. The subdural hyperintense bands accounted for almost all high intensity areas in the subdural hematomas.…”
Section: Discussionmentioning
confidence: 70%
“…The high intensity bands may reflect extracellular and/or intracellular methemoglobins without the influence of water molecular diffusion because the ADC value (0.76 ± 0.24 × 10 -3 mm 2 /sec) of the high intensity areas in the chronic subdural hematomas was similar to the reported ADC values of the extracellular (0.58 ± 0.10 × 10 -3 mm 2 /sec) and/or intracellular (0.55 ± 0.23 × 10 -3 mm 2 /sec) methemoglobins. 8) Repeated hemorrhaging from the outer membrane has been considered to be a causative factor of the chronic subdural hematoma. 6,21) Intravenous infusion of 51 Cr-labeled red blood cells in patients with chronic subdural hematoma resulted in the subsequent presence of labeled cells in the subdural fluid.…”
Section: Discussionmentioning
confidence: 99%
“…All personal identifiers were removed from the data spreadsheets such that there were no links between the study sequence folders and the individual patients as shown in Figure 1. Each radiologist documented his results into positive or negative restricted diffusion for infarction via analysis of restricted DWI & ADC mapping, blooming artifact seen on gradient sequencing, perfusion deficit as determined by analysis of cerebral blood flow, cerebral blood volume, and mean transit time [38][39][40][41][42][43]. In addition, other CNS pathologic etiologies were assayed including: intracranial hemorrhage, spinal cord compression, fracture, spinal canal stenosis, neural foraminal stenoses, disk herniation, and annular fissuring [24,[44][45][46][47].…”
Section: Methodsmentioning
confidence: 99%